Endophytic Beauveria bassiana in sugarcane and associated Eldana saccharina host plants in South Africa - Nongcebo S. Memela; R. Stuart Rutherford; Stefan Schmidt (BioControl, 2024)
Eldana saccharina Walker is a problematic sugarcane stalk borer pest in South Africa. Twenty-eight sugarcane genotypes ( Saccharum spp. hybrids) and seven different species of host plants of E. saccharina were surveyed for the presence of endophytic Beauveria bassiana sensu lato ( s.l. ). Collectively, 326 plant samples (roots, stems, or leaves) were collected from five locations in sugarcane-producing areas (KwaZulu-Natal; South Africa). Following plant surface disinfection, 128 fungal colonies morphologically resembling Beauveria spp. were isolated from internal plant tissues. The sequence analysis of the internal transcribed spacer region confirmed that 13 representative isolates were B. bassiana. s.l . Eight B. bassiana isolates were recovered from E. saccharina natural host plants, and 120 from different sugarcane stem parts (top node, top internodes, bottom node, and bottom internode). Endophytic B. bassiana isolates were recovered from 22 of 28 sugarcane genotypes surveyed. The number of B. bassiana isolates obtained from different sugarcane parts differed significantly, with more B. bassiana isolates obtained from the top than the bottom internodes. Furthermore, sugarcane genotypes N31 and N41 yielded B. bassiana from all plant parts sampled, while five sugarcane genotypes harbored no B. bassiana isolates. This study demonstrates for the first time the natural occurrence of endophytic B. bassiana strains in sugarcane plants and E. saccharina host plants in South Africa.